Funcionalismo público: Dois regimes históricos - Valdir Melo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– To shape or to choose an appropriate regime of civil service is an old problem. The modern State in the West adopted two regimes in its first experience, the sale of public offices and favoritism. History and situational-strategic analysis derive lessons from that experience. In the first option, the State tends to lose control of those functions of public interest and to favor the interests of the buyers of public offices. In the second option, favoritism tends to submit society to a small social stratum. This stratum controls the occupation of positions of authority in the State, the legal norms, the actions of regulation, as well as other institutions that may give economic advantages or benefits of other kinds.
10419/284878
Keywords: D73; A13; B40; 330; regimes of civil service; sale of public offices; favoritism